DEVELOPMENT OF NEW MATERIALS FOR KITCHENWARE: DISCOVERING INNOVATIVE MATERIALS TO IMPROVE EFFICIENCY AND SAFETY IN THE KITCHEN - Pereira, Karliano Antônio Rôla (Revista Sistemática, 2020)
The development of innovative materials for kitchenware plays a critical role in enhancing cooking efficiency, safety, and sustainability. This article reviews recent advances in materials science applied to kitchen utensils, highlighting the integration of nanotechnology, bio-based polymers, high-entropy alloys, and smart materials. Emphasis is placed on improving thermal management, antimicrobial properties, environmental impact, ergonomic design, and the incorporation of smart sensing technologies. The exploration of biodegradable composites and multifunctional coatings addresses both consumer health concerns and ecological challenges. Future trends indicate a convergence of material innovation and digital integration, promising safer, more efficient, and environmentally responsible kitchen tools.